The genome sequence of the sycamore, Acronicta aceris (Linnaeus, 1758) - Boyes, D; Crowley, LM; Holland, PWH (F1000Research, 2021)
We present a genome assembly from an individual female Acronicta aceris (the sycamore; Arthropoda; Insecta; Lepidoptera; Noctuidae). The genome sequence is 466 megabases in span. The complete assembly is scaffolded into 32 chromosomal pseudomolecules, with the W and Z sex chromosome assembled.